2023
DOI: 10.1242/dev.201660
|View full text |Cite
|
Sign up to set email alerts
|

Partial male-to-female reprogramming of mouse fetal testis by Sertoli cell ablation

Abstract: Temporal transcription profiles of fetal testes with Sertoli cell ablation were examined in 4-day culture using a diphtheria toxin (DT)-dependent cell knockout system in AMH-TRECK transgenic (Tg) mice. RNA analysis revealed that ovarian-specific genes, including Foxl2, were ectopically expressed in DT-treated Tg testis explants initiated at embryonic days 12.5–13.5. FOXL2-positive cells were ectopically observed in two testicular regions—near the testicular surface epithelia and around its adjacent mesonephros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…In this study, we found that the specific marker genes for Sertoli cells ( gsdf and fgf2 ) and Leydig cells ( igf2 and bmp4 ) were significantly expressed in a cell cluster from the juvenile testes, suggesting that the Sertoli cells and Leydig cells may be differentiated from the same cell precursor. Although the origin of Sertoli and Leydig cells in fish is not fully understood, the fetal Sertoli cells were well known to induce appearance of Leydig cells in mammals (Imaimatsu et al, 2023; Yao and Rodriguez, 2023). Our findings offer valuable insights for further research into the origin of gonadal somatic cells in fish.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the specific marker genes for Sertoli cells ( gsdf and fgf2 ) and Leydig cells ( igf2 and bmp4 ) were significantly expressed in a cell cluster from the juvenile testes, suggesting that the Sertoli cells and Leydig cells may be differentiated from the same cell precursor. Although the origin of Sertoli and Leydig cells in fish is not fully understood, the fetal Sertoli cells were well known to induce appearance of Leydig cells in mammals (Imaimatsu et al, 2023; Yao and Rodriguez, 2023). Our findings offer valuable insights for further research into the origin of gonadal somatic cells in fish.…”
Section: Discussionmentioning
confidence: 99%